Anti-inflammatory and redox-protective activities of citronellal - Melo, Mônica Santos de (2011)
The anti-inflammatory and redox protective effects of the citronellal (CT) were evaluated using in vivo and in vitro tests. Intraperitoneal (i.p.) administration of CT (50, 100, and 200 mg/kg) inhibited (p < 0.05) the carrageenan-induced leukocyte migration to the peritoneal cavity. Additionally, the carrageenan- and arachidonic acid-induced rat hind paw edema was significantly inhibited (p < 0.05) by i.p. administration of 100 and 200 mg/kg of the compound. When the redox activity was evaluated, CT (200 mg/kg) significantly reduced hepatic lipoperoxidation (p < 0.001), as well as oxidation of plasmatic (p < 0.05) and hepatic (p < 0.01) proteins. The results of the present study support the hypothesis that CT possesses anti-inflammatory and redox protective activities. It is suggested that its effects are associated with the inhibition of the enzymes in the arachidonic acid pathway, which prevent cell migration by inhibiting leukotriene production, edema formation and the increase of reactive oxygen species in tissues. Therefore, CT is of potential benefit to manage inflammatory disorders and correlated damages caused by oxidant agents.